Design and analysis of an integrated pulse modulated S-band power amplifier in gallium nitride process - Sedlock, Steve (Kansas State University, 2012)
The design of power amplifiers in any semi-conductor process is not a trivial exercise and it is often encountered that the simulated solution is significantly different than the results obtained. Oscillatory phenomena occurring either in-band or out of band and sometimes at subharmonic intervals can render a design useless. Other less apparent effects such as jumps, hysteresis and continuous spectrum, often referred to as chaos, can also invalidate a design. All of these problems might have been identified through a more rigorous approach to stability analysis. Designing for stability is probably the one area of amplifier design that receives the least amount of attention but incurs the most catastrophic of effects if it is not performed properly. Other parameters such as gain, power output, frequency response and even matching may have suitable mitigation paths. But the lack of stability in an amplifier has no mitigating path. In addition to the loss of the design there are the increased production cycle costs, costs involved with investigating and resolving the problem and the costs involved with schedule slips or delays resulting from it. The Linville or Rollett stability criteria that many microwave engineers follow and rely exclusively on is not sufficient by itself to ensure a stable and robust design. It will be shown that the belief that unconditional stability is obtained through an analysis of the scattering matrix S to determine if K>1 and [delta][supscript]s<1 can fail and other tools must be used to validate circuit stability. With the emphasis being placed on stability, a 1W pulse modulated S-band power amplifier is designed using a battery of analysis tools in addition to the standard Linville or Rollett criteria to rigorously confirm the stability of the circuit. Test measurements are then presented to confirm the stability of the design and illustrate the results. The research shown contributes to the state of the art by offering a detailed approach to stability design and then applying the techniques to the design of a 1W pulse modulated S-band power amplifier demonstrating the first with 20 nanosecond pulse width switching and single digit nanosecond rise and fall times at 1 Watt power levels.
Keywords: Amplifier stability; Normalized Determinant Function; Auxiliary generator; Gallium Nitride; Engineering (0537)